ANALISIS RISIKO PRODUKSI USAHATANI PADI LAHAN BASAH DAN LAHAN KERING DI KABUPATEN MELAWI - RAMA, ROFINUS; NURLIZA, NURLIZA; DOLOROSA, EVA (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2016)
This study aims to analyze the production risk of rice farm and compare production risk betwen wetland rice farm and field rice farm. The method used in this study is deskriptive and quantitative method. The location is determined by purposive. Data obtained through interviews with160 randomly simple rice farmers. The method used is just and pope production of multiple linear regression analysis with cobb douglas method and t test analysis.The results of this research were: the model showed that the factors such as land width, seeds, urea fertilizers, pesticides and quantity of family labours had a real influence to the increase of the wetland rice farm production. While NPK fertilizers, age and education of farmers did not influence to (non-significant) the increasing of rice production.The model used in this research had showed that land width, pesticides, quantity of family labours and age of farmers had a real influence to the increase of the field rice farm production. While seeds and education farmer did not influence to (non-significant) the increasing of rice production. Compare production risk between wetland rice farm and field rice farm showed real difference. Keywords: Risk, Production, Rice Farm, wetland and field.